Visual Web-Oriented Environment of Dynamic Control of Data Flow in Campus of Software Defined Networks - Vyacheslav P. Koryachko; Dmitry A. Perepelkin; Maria A. Ivanchikova; Vladimir S. Byshov (Моделирование и анализ информационных систем, 2019)
Nowadays new innovative approaches based on the technology of software defined networks (SDN) are gaining popularity in the field of computer networks (CN). SDN provide a flexible approach to the processing and control of data flows in CN by separating the control plane and data plane, as well as centralizing the representation of the entire network. In this paper, we propose a software infrastructure and a visual web-oriented environment (SIVE) for dynamic control of data flows in campus SDN based on OpenFlow protocol. It was proposed to use the SIVE as an integrated segment of the campus network of Ryazan State Radio Engineering University. The aim of the work is the development of the SIVE architecture in the form of UML class diagram description, as well as the creation of software methods for organizing effective network interaction of various software systems in SDN based on OpenFlow protocol. A hardware-software test bench based on HP Aruba 2920-24G equipment was developed to confirm the efficiency and reliability of the proposed SIVE. The offered SIVE is the basis for the development of a large class of software systems and SDN components based on OpenFlow protocol.